Entrepreneur Voices on Company Culture. - Lewis, Derek; Feifer, Jason (Entrepreneur Voices., 2018)
No longer just a buzz term, company culture has gone from something employees would like to have to something they must have. Studies show that companies who invest in their culture can see a performance increase of 20-30 percent-making it hard to overlook things like a strong and positive vision, values and beliefs that impact both employee happiness and their bottom line. With this culture-focused edition of the Entrepreneur Voices series, the staff of Entrepreneur provides an exclusive compilation of editorial articles, advice from entrepreneurs, and reflections and various culture styles,